Comorbid anxiety, loneliness, and chronic pain as predictors of intervention outcomes for subclinical depressive symptoms in older adults: evidence from a large community-based study in Hong Kong - Stephanie Ming Yin Wong; Dara Kiu Yi Leung; Tianyin Liu; Zuna Loong Yee Ng; Gloria Hoi Yan Wong; Wai Chi Chan; Terry Yat Sing Lum (BMC Psychiatry)
Abstract Background Depression is among the leading causes of the global burden of disease and is associated with substantial morbidity in old age. The importance of providing timely intervention, particularly those with subclinical symptoms, has thus increasingly been emphasised. Despite their overall effectiveness, a small but notable subgroup tends to be less responsive to interventions. Identifying predictors of non-remission and non-response is critical to inform future strategies for optimising intervention outcomes. Methods A total of 4153 older adults aged 60 years and above with subclinical depressive symptoms (Patient Health Questionnaire-9 [PHQ-9] = 5–19) were recruited from JC JoyAge, a large-scale collaborative stepped-care intervention service across Hong Kong. A wide range of clinical and modifiable risk and protective factors at baseline were assessed, including depressive symptoms, anxiety symptoms, loneliness, suicidal ideation, cognitive capacity, multimorbidity, chronic pain, need for informal care due to mental health reasons, history of abuse, and sociodemographic characteristics. Separate multivariable logistic regression models were applied to identify predictors of non-remission (PHQ-9 ≥ 5) and non-response (< 50% reduction in PHQ-9) following intervention. Results The rates of non-remission and non-response were 18.9% (n = 784) and 23.0% (n = 956), respectively. Comorbid anxiety symptoms (adjusted odds ratio [aOR] = 2.08, CI = 1.72–2.51; 1.28, 1.05–1.57), loneliness (2.00, 1.66–2.42; 1.67, 1.38–2.01), need for informal care (1.86, 1.49–2.33; 1.48, 1.18–1.85), lower cognitive capacity (0.95, 0.93–0.97; 0.94, 0.92–0.96), and absence of chronic pain (0.59, 0.48–0.72; 0.76, 0.64–0.91) predicted both non-remission and non-response. Meanwhile, moderate-to-severe depressive symptoms predicted higher odds of non-remission (1.41, 1.18–1.69) and lower odds of non-response (0.28, 0.23–0.34), respectively. Subgroup analyses conducted separately in older adults with mild and moderate-to-severe depressive symptoms at baseline revealed that comorbid anxiety, loneliness, need for informal care, and absence of chronic pain were consistent predictors of non-remission. Those with non-remission and non-response showed more depression-related functional impairments and poorer health-related quality of life post-intervention. Conclusions Older adults with subclinical depressive symptoms showing comorbid anxiety, higher loneliness, need for informal care, and chronic pain may be offered more targeted interventions in future services. A personalised risk-stratification approach may be helpful. Trial registration ClinicalTrials.gov identifiers: NCT03593889 (registered 29 May 2018), NCT04863300 (registered 23 April 2021).